2023
DOI: 10.3390/ijerph20021379
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Effect of Energy Intensity on Carbon Emission Reduction in Beijing

Abstract: Beijing has experienced rapid economic development since the reforms and opening up. However, the traditional development model based on excessive energy consumption has posed great challenges to the ecological environment. To curb environmental degradation and achieve sustainable social development, Beijing has proposed to achieve carbon neutrality by 2050. As an important indicator of energy consumption, it is necessary to clarify how energy intensity (EI) affects carbon emissions (CE) to achieve carbon neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…This is attributed to RENC effects. This outcome is supported by the studies of (Danish, Ulucak, & Khan, 2020; Li et al, 2023).…”
Section: Analysis and Interpretationsupporting
confidence: 61%
See 2 more Smart Citations
“…This is attributed to RENC effects. This outcome is supported by the studies of (Danish, Ulucak, & Khan, 2020; Li et al, 2023).…”
Section: Analysis and Interpretationsupporting
confidence: 61%
“…Somoye, Ozdeser, et al (2023) found a similar outcome for Brazil. Li et al (2023) found a negative association for Beijing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For the indicators with greater impact, similar conclusions were drawn in previous studies on CO 2 emissions in Beijing's transportation sector. Li et al [75] pointed out that transportation energy intensity is a significant main driving factor for CO 2 emission reduction in the transportation sector. Further research showed that transportation energy intensity, economic development, population size, and transportation turnover intensity are also major factors affecting Beijing's transportation CO 2 emissions [66][67][68]70,71].…”
Section: The Results Of Ridge Regressionmentioning
confidence: 99%
“…The growth in population size will lead to an increasing demand for energy consumption, and in turn to more carbon emissions [55]. The total energy consumption is closely related to the economic growth, environmental regulation, industry structure and other factors, and the reduction in energy intensity and energy structure is influenced by other factors that will directly contribute to carbon emissions [56,57].…”
Section: System Boundarymentioning
confidence: 99%